1985
DOI: 10.1021/ac00286a050
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous molecular and atomic spectrometry with electrothermal atomization and diode array detection

Abstract: Sir: Some papers dealing with the ultraviolet and visible study of molecular vapors produced by electrothermal atomizers were recently published (1-5). Various instruments were proposed depending on the aim of the work, from conventional flameless atomic absorption spectrometers (1-4) to dedicated equipment (5).Recently also the infrared range has been investigated, coupling an FT-IR spectrometer with a heated graphite atomizer, thus introducing further analytical applications of this device (6). At the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…RESULTS AND DISCUSSION Absorption Spectra. Absorbance spectra for several elements have been previously reported for a graphite furnace CSAAS experiment using a diode array for a detector (14,15). These works focused on simultaneous molecular and atomic absorption measurements; the resolution of the atomic lines was poor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RESULTS AND DISCUSSION Absorption Spectra. Absorbance spectra for several elements have been previously reported for a graphite furnace CSAAS experiment using a diode array for a detector (14,15). These works focused on simultaneous molecular and atomic absorption measurements; the resolution of the atomic lines was poor.…”
Section: Methodsmentioning
confidence: 99%
“…These works focused on simultaneous molecular and atomic absorption measurements; the resolution of the atomic lines was poor. Nevertheless, lead, copper, manganese, zinc, cadmium, vanadium, and nickel were determined in various crude oils and pigments (14), and matrix chloride interferences were characterized in the determination of copper and manganese (75).…”
Section: Methodsmentioning
confidence: 99%
“…The further drawback arising from the sequential read-out of the array can be circumvented by means of a mechanical shutter. At first, linear PDA detectors were used in AAS for the study of broadrange background absorption in the graphite furnace [105,106]. By means of a D 2 lamp as continuum source the wavelength range from 190 nm to 350 nm could be covered with a bandwidth per pixel of a few hundred pm.…”
Section: Linear Photodiode Arrays (Pdas)mentioning
confidence: 99%
“…It is also possible that larger clusters of sulfur existed which were responsible for the formation of S 1 and S 2 1 through fragmentation. Hearly et al 18 identified cationic sulfur by laser ablation and obtained a positive ion spectrum which showed a greater range of sulfur species from S 1 to S 11 1 . Larger clusters were reported to have existed over a small range of low laser power while S 1 dominated at high laser powers.…”
Section: At 219 Nmmentioning
confidence: 99%
“…ETV with a continuous source of radiation and an ultraviolet (UV) multichannel detector spectrometer was employed recently for the systematic study of UV absorption spectra of inorganic compounds. [1][2][3][4][5][6][7][8][9][10][11][12][13] The setup was initially developed by Tittarelli et al, [1][2][3][4] and later improved by Daminelli et al [5][6][7] Investigations of alkaline earth fluorides and chlorides, [8][9][10] indium nitrate and Group 3 halides, 11 sulfides, sulfates and sulfur 12,13 were also carried out with this technique. The main objective of these studies was to identify species responsible for the absorption of the UV radiation.…”
Section: Introductionmentioning
confidence: 99%